183k views
2 votes
What is the quotient (3x2 + 8x − 3) ÷ (x + 3)?

User Willin
by
6.4k points

2 Answers

1 vote

Answer:

3x−1

Explanation:

3x^2+8x−3/x+3

=3x2+8x−3/x+3

=(3x−1)(x+3)/x+3

=3x−1

User Edward DiGirolamo
by
5.9k points
3 votes

Answer:

3x-1

Explanation:

We have the following expression:


(3x^2+8x-3)/(x+3)

Equating this equal to zero and completing the square then to get:


3x^2+8x-3=0

Arranging the terms which contain the same variable and moving the constant to the opposite side of the equation:


3x^2+8x=3

Factorize the leading coefficient:


3(x^2+(8x)/(3) )=3

Now complete the square and do not forget to balance the equation by adding the same constants to each side.


3(x^2+(8x)/(3) +(16)/(9) )=3+(16)/(3)


3(x^2+(8x)/(3) +(16)/(9) )=(25)/(3)


(x^2+(8x)/(3) +(16)/(9) )=(25)/(9)

Re-writing it as perfect square:


(x+(4)/(3) )^2=(25)/(9)

Taking square root at both sides to get:


x+(4)/(3) =+-(5)/(3)


x=-(4)/(3) +(5)/(3) ,x=-(4)/(3) -(5)/(3)


x=(1)/(3) , x=-3

So,
3x^2+8x-3=3(x-(1)/(3))(x+3) =(3x-1)(x+3)

Substiting it:


(3x^2+8x-3)/(x+3) =
((3x-1)(x+3))/((x+3)) = (3x-1)


User Sefa
by
5.9k points